Impaired Topographical Organization of Functional Brain Networks in Parkinson’s Disease Patients With Freezing of Gait - Ruan, Xiuhang; Li, Yuting; Li, E.; Xie, Fang; Zhang, Guoqin; Luo, Zhenhang; Du, Yuchen; Jiang, Xinqing; Li, Mengyan; Wei, Xinhua (Frontiers in Aging Neuroscience, 2020)
Objective: The aim of this study was to explore alterations in the topological properties of the functional brain network in primary Parkinson’s disease (PD) patients with freezing of gait (PD-FOG). Methods: Resting-state functional magnetic resonance imaging (Rs-fMRI) data were obtained in 23 PD-FOG patients, 33 PD patients without FOG (PD-nFOG) and 24 healthy control (HC) participants. The whole-brain functional connectome was constructed by thresholding the Pearson correlation matrices of 90 brain regions, and topological properties were analyzed by using graph theory approaches. The network-based statistics (NBS) method was used to determine the suprathreshold connected edges (P < 0.05; threshold T = 2.725), and statistical significance was estimated by using the nonparametric permutation method (5000 permutations). Statistically significant topological properties were further evaluated for their relationship with clinical neurological scales. Results: The topological properties of functional brain network in PD-FOG and PD-nFOG showed no abnormalities at the global level. However, compared with HCs, PD-FOG patients showed decreased nodal local efficiency in several brain regions, including bilateral striatum, fronto-parietal areas, visual cortex and bilateral superior temporal gyrus, increased nodal local efficiency in left gyrus rectus. When compared with PD-nFOG patients and HCs, PD-FOG showed increased betweenness centrality in left hippocampus. Moreover, compared to HCs, both PD-FOG and PD-nFOG patients displayed reduced network connections by using the NBS method, mainly involving the sensorimotor cortex, visual network, default mode network, auditory network, dorsal attention network, subcortical regions and limbic network. The local node efficiency of the right temporal pole: superior temporal gyrus in PD-FOG patients was positively correlated with Freezing of Gait Questionnaire (FOGQ) scores. Conclusions: This study demonstrates the disrupted regional topological organization in PD-FOG patients, especially associated with damage to the subcortical regions and multiple cortical regions. Our results provide insights into the dysfunctional mechanisms of the relevant networks and indicate potential neuroimaging biomarkers of PD-FOG.